Pengaruh Genre dan Storyline Terhadap Keputusan Menonton Film Agak Laen - Muhammad Arsalan Ainin; Urip Mulyadi (Indo Publishing, 2025)
This study aims to determine the influence of genre and storyline on the decision to watch the movie Agak Laen. The study applies the Uses and Gratification theory with a quantitative approach. Data were collected through questionnaires distributed to 100 respondents. Hypothesis testing was conducted using t-test, F-test, and the coefficient of determination (R²) with SPSS version 27. The results show that (1) genre has a significant influence on the decision to watch (t count 3.712 > t table 1.661; sig. 0.01 < 0.05), (2) storyline has a significant influence on the decision to watch (t count 6.159 > t table 1.661; sig. 0.01 < 0.05), and (3) genre and storyline simultaneously have a significant influence on the decision to watch (F count 73.020 > F table 3.09; sig. 0.01 < 0.05). The coefficient of determination (R²) was 0.601, meaning that 60.1% of the decision to watch is influenced by genre and storyline, while the remaining 39.9% is influenced by other factors.